Mechanochemically assisted synthesis of titanium carbonitride from metal and organic precursor. Issue 11 (3rd July 2020) - Liu, Shaocun; Li, Baozhong; Wu, Yingju; Luo, Kun; Zhao, Zhisheng; Zhang, Yang
Abstract: Ultrafine TiC0.29 N0.38 powders with a particle size of approximately 170 nm were synthesized by mechanochemical synthesis combined with moderate‐temperature annealing using Ti and ethylenediamine as raw materials. Ethylenediamine plays a versatile role in the fabrication of ultrafine TiC x N y powders. It can serve as not only carbon and nitrogen sources, but also a process control agent, that facilitates the generation of ultrafine particles. A dense TiC0.3 N0.39 ceramic with a high hardness of 16.7 GPa was obtained by spark plasma sintering at a considerably reduced temperature of 1100°C. This simple, energy‐efficient method is a novel approach to synthesizing valuable TiC x N y .